Higher Time to Peak after Stent Implantation in Symptomatic High-Grade Intracranial Atherosclerotic Stenosis is Related to In-Stent Restenosis - Zhang, Longhui; Zhu, Haoyu; Zhang, Yupeng; Chen, Fangguang; Sun, Dapeng; Liu, Yufan; Jiang, Chuhan; Miao, Zhongrong; Jia, Baixue (Translational stroke research, 2025)
Little is known about the association between periprocedural hemodynamics and in-stent restenosis (ISR) following stent implantation in patients with symptomatic intracranial atherosclerotic stenosis (ICAS). This study aims to identify periprocedural hemodynamics that may be associated with ISR. Subjects were selected from the NOVA trial (The First-in-man Trial Evaluating the Safety and Efficacy of the NOVA Intracranial Stent Trial). ISR was defined as greater than 50% stenosis of the luminal diameter within or immediately adjacent to (within 5 mm) the implanted stent. Periprocedural hemodynamics, including cerebral blood flow, cerebral blood volume, mean transit time, and time to peak (TTP), were derived from the time-density curve generated from digital subtraction angiography using the fast Fourier transform algorithm. Of the 263 patients enrolled in the NOVA trial, 176 with symptomatic high-grade ICAS who underwent stent implantation were included in this study. Of these, 35 (19.9%) were diagnosed with ISR at the one-year follow-up. No significant differences in pre-procedure hemodynamics were observed between stent groups and between the ISR groups and the non-ISR group. Higher post-procedure TTP (OR, 1.95; 95% CI, 1.26–3.02), the use of bare-metal stents (OR, 5.40; 95% CI, 2.21–13.19), and higher post-procedure residual stenosis (OR, 1.08; 95% CI, 1.03–1.13) were independent factors associated with ISR. Higher post-procedure TTP, the use of bare-metal stents, and higher post-procedure residual stenosis were independent factors associated with ISR. The combined use of periprocedural hemodynamics and clinical factors may help predict ISR in patients with symptomatic high-grade ICAS. Graphical Abstract